Molecular and phenotypic characterization of Streptococcus pneumoniae isolates in a Japanese tertiary care hospital - Nakao, Takumi; Kosai, Kosuke; Akamatsu, Norihiko; Ota, Kenji; Mitsumoto-Kaseida, Fujiko; Hasegawa, Hiroo; Izumikawa, Koichi; Mukae, Hiroshi; Yanagihara, Katsunori (Frontiers in Cellular and Infection Microbiology, 2024)
This study aimed to investigate the bacterial characteristics of pneumococcal isolates obtained from a tertiary care hospital in Japan. We analyzed the antimicrobial susceptibility, possession of macrolide resistance genes, pneumococcal serogroup/serotype, and sequence type (ST) of pneumococcal isolates from patients aged 15 years or older between 2011 and 2020 at Nagasaki University Hospital. Of the 73 isolates analyzed, 86.3% showed resistance to macrolides, and 28.8%, 46.6%, and 11.0% harbored mefA, ermB, and both, respectively. Of the isolates possessing ermB, 97.6% showed high levels of macrolide resistance [minimal inhibitory concentration (MIC) range, > 16 µg/mL]. Solithromycin (MIC range, 0.03–0.25 µg/mL), regardless of the presence of macrolide resistance genes, and lascufloxacin (MIC range, 0.06–0.5 µg/mL) showed potent in vitro activity against pneumococci. Serotype 19A was the most prevalent (six isolates), followed by serotypes 10A, 15A, and 15B/C (five isolates each). Four serotypes (11A, 19A, 22F, and 23B) and five STs (36, 99, 433, 558, and 3111) were significantly correlated with the presence of macrolide resistance genes. All four isolates with serotype 11A/ST99 and three isolates with serotype 19A/ST3111 harbored both mefA and ermB. No macrolide resistance genes were detected in either of the two isolates with serotype 22F/ST433, while all ten isolates with serogroup 15 (serotypes 15A and 15B/C, five isolates each) possessed ermB alone. Our study revealed the bacterial characteristics of the pneumococcal isolates obtained from our hospital. In vitro activity of solithromycin and lascufloxacin against these isolates was confirmed.